Assessing durability properties of noise barriers made of concrete incorporating bottom ash as aggregates. Issue 12 (2nd December 2019) - Leiva, Carlos; Arenas, Celia; Vilches, Luis F.; Arroyo, Fatima; Luna-Galiano, Yolanda
Abstract: This research analyses the durability of a noise barrier using coal bottom ashes as aggregates in a high proportion (80%wt of bottom ash). A concrete noise barrier is composed by a combination of a porous sound absorbing face and a standard concrete in order to increase the mechanical properties of the barrier. The bottom ash was sieved at 2.5 mm, a porous concrete with the coarse fraction of bottom ashes and a standard concrete with the fine fraction of bottom ashes were made. This paper analyses the water absorption, resistance to acid attacks, resistance to sulphate attacks and resistance to freeze-thaw cycles, determining mechanical and acoustical properties of the porous concrete. When the materials are subjected to acid and sulphate attacks, the compressive strength is reduced to 20% and the noise absorption to 40% from initial baseline. When all the materials are subjected to freeze-thaw cycles, a mass loss higher than 15% at 30–40 cycles was observed, the compressive strength of materials with a high particle size drops at 20–30 cycles for natural and bottom ashes aggregates, and the noise absorption of bottom ash materials present a lower drop than natural aggregates.